Diagnostic Dilemma in a Young Woman with Acute Headache: Delayed Diagnosis of Third Ventricular Colloid Cyst with Hydrocephalus - Jasem Y. Al-Hashel; Azza A. H. Rady; Doaa Y. Soliman; Periasamy Vembu (Case Reports in Neurological Medicine)
Objectives. To highlight the importance of early diagnosis of colloid cyst of the third ventricle and its early management. Clinical Presentation and Intervention. This is a young lady who presented with sudden onset headache. She attended a local clinic and also her area hospital. Her diagnosis was delayed several hours due to a diagnostic dilemma initially. No surgical intervention was tried since the patient developed early signs of brainstem coning by the time she was seen by neurosurgeon. Patient died after few days in spite of intensive ICU measures. Conclusion. Sudden onset headache in young adults should be looked at carefully. Early imaging is mandatory to prevent mortality.